2022
DOI: 10.1002/bse.3036
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive performance measurement framework for business incubation centres: Empirical evidence in an Irish context

Abstract: During the last 20 years, there has been an increased interest among academics and practitioners in the area of business incubation. However, limited attention has been devoted to developing a comprehensive framework that can measure business incubators' performances. Therefore, there is an urgent need for an appropriate, robust and useable performance framework. In this paper, we present a comprehensive framework using a weighted fuzzy inference system for business incubation centres' (BIC) performance measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…A limited number of studies have explored the context of BICs. This is despite the importance of BICs for a functioning regional innovation ecosystem (Azadnia et al 2022).…”
Section: Conclusion and Contributionsmentioning
confidence: 96%
See 2 more Smart Citations
“…A limited number of studies have explored the context of BICs. This is despite the importance of BICs for a functioning regional innovation ecosystem (Azadnia et al 2022).…”
Section: Conclusion and Contributionsmentioning
confidence: 96%
“…The impact of business incubation on successful business development has received increased attention (Sagath et al, 2019). Variances in incubation models has led to a dominant focus on the facilities, services and activities related to business incubation (Azadnia et al, 2022) and how these differ across different types of incubators. In this research we explored a particular type of business incubation, Business Incubation Centers (BICs) which are regionally based across Ireland.…”
Section: Conclusion and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the identified gap this study seeks to address is well known (Hausberg & Korreck 2020:160), there have been an increasing number of attempts to propose comprehensive frameworks for evaluating incubator efficacy. A recent attempt by Azadnia et al (2022Azadnia et al ( :2415 identified a variety of criteria relevant to the Irish incubation ecosystem; however, their approach focused heavily on the performance of the incubators in terms of facilities and infrastructure and by their own admission, identified a need to shift focus towards the efficacy of factors relevant to the incubation activity, such as networks and availability of fundings.…”
Section: Approaches To Investigating Incubator Efficacymentioning
confidence: 99%
“…Improved financial management capabilities, often resulting from financial literacy and training initiatives, enable incubated entrepreneurs to navigate the complexities of Tanzania's semi-formal financial systems more effectively (Azadnia et al, 2022). They become more aware of the various semi-formal financing options available to them, understand the associated risks and benefits, and can make informed decisions that optimize their financial accessibility.…”
Section: Introductionmentioning
confidence: 99%